THE PRINCIPAL’S STRATEGIES FOR BUILDING READING CULTURE IN SDN 131/IV JAMBI - Yantoro (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Students’ reading skill has a big influence for students in determining their success in learning process. Students who are able to read well and faster will achieve good learning outcomes. By knowing the importance of reading skills, school must be able to build students’ reading culture. This study aims to find out the principal's strategy in building the students’ reading culture. This research used a qualitative descriptive approach. This research located at SDN 131 / IV Jambi. The subjects of the research were the principal and the teacher. Data collection techniques were observation, interviews and documentation. Data analysis techniques were reduction, display and verification. The results showed that the principal's strategy in building students’ reading culture were carried out with habituation, exemplar, cooperation, provision of facilities and infrastructure as well as a reading clinic. This study concluded that the principal's strategy in building students’ reading culture in the school were by forming a reading habit before starting learning process, being an exemplar by reading along with teachers and students, providing reading culture clinics for teachers and students and building cooperation with institutions such as Tanoto Foundation.